2015
DOI: 10.1111/ejn.13068
|View full text |Cite|
|
Sign up to set email alerts
|

Nerve regeneration in chitosan conduits and in autologous nerve grafts in healthy and in type 2 diabetic Goto–Kakizaki rats

Abstract: Knowledge about nerve regeneration after nerve injury and reconstruction in appropriate diabetic animal models is incomplete. Short-term nerve regeneration after reconstruction of a 10-mm sciatic nerve defect with either a hollow chitosan conduit or an autologous nerve graft was investigated in healthy Wistar and diabetic Goto-Kakizaki (GK) rats. After 21 days, axonal outgrowth, the presence of activated and apoptotic Schwann cells and the thickness of the formed matrix in the conduits were measured. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 41 publications
(63 reference statements)
2
47
0
2
Order By: Relevance
“…The described procedures have been performed in different previous studies and are routine procedures to analyze the regenerating conditions short-term after peripheral nerve reconstruction with tubular grafts [7, 10, 11, 14]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The described procedures have been performed in different previous studies and are routine procedures to analyze the regenerating conditions short-term after peripheral nerve reconstruction with tubular grafts [7, 10, 11, 14]. …”
Section: Resultsmentioning
confidence: 99%
“…Activated Schwann cells, defined as ATF-3 stained Schwann cells [10, 11, 14], were observed in the formed regenerative matrix in generally small proportions (median values 6.0–16.8%). The values displayed no significant differences between the groups (Table 2; it should be recognized that only few matrices were available for immunostaining in the middle of the conduit, particularly in the hCNG-I healthy samples).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional recovery of the nerve was assessed using the Basso, Beattie, and Bresnahan (BBB) locomotor rating scale for rat hind limb motor function [16]. Although BBB is widely used to assess functional recovery in spinal cord injured animals, however, it has been demonstrated that it could be most useful in assessment of never repair processes in peripheral nerve injuries [17].…”
Section: Behavioral Testingmentioning
confidence: 99%
“…Chitosan is a polysaccharide derived from chitin, it is biocompatible, and it can promote glial cells survival and neurite outgrowth [8][9][10]. It has been shown that hollow chitosan tube can be effective as autologous nerve graft for bringing 10-mm gap in rat sciatic nerve model [7,11,12]. In order to increase the performance of chitosan tube for long defect repair; here, we filled the tube with a hydrogel, called NVR gel, composed mainly by hyaluronic acid and laminin.…”
Section: Introductionmentioning
confidence: 99%